FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM MELAKUKAN PEMBELIAN BAHAN BANGUNAN PADA TOKO DELTA DI KABUPATEN MAMUJU - Juniarni, Selvi; Ratna, Ratna (LPPM Universitas Muhammadiyah Mamuju, 2023)
This research is entitled factors that influence consumer behavior in purchasing building materials at Delta stores in Mamuju Regency. The aim of the research is to determine how culture, social, personal and psychology partially influence consumers in purchasing building materials at Delta stores in Mamuju Regency and to determine the influence of consumer behavior and consumer psychology simultaneously on decisions to purchase building materials. The results of the research partially show that culture influences consumer behavior in purchasing building materials and simultaneously shows that social, personal and psychological culture influences consumers in purchasing building materials at Delta stores in Mamuju Regency and provides solutions for developing businesses to increase sales in delta shop in Mamuju Regency, consumer behavior in cultural aspects such as paying attention to consumer habits in making purchases because of the cultural respondents' responses which have a small dominant average compared to other elements of consumer behavior and consumer behavior is not easy to understand because each individual consumer has different behavior -different in purchasing building materials.